Mythology : Tmeless Tales of Gods and Heroes - Hamilton, Edith, 1867-1963. (New York : Grand Central Pub., 2011)
Monsters, mortals, gods, and warriors: For over sixty years readers have chosen this book above all others to discover the thrilling, enchanting, and fascinating world of Western mythology. From Odysseus's adventure-filled journey to the Norse god Odin's effort to postpone the final day of doom, Edith Hamilton's classic collection not only retells these stories with brilliant clarity but shows us how the ancients saw their own place in the world and how their themes echo in our consciousness today. An essential part of every home library, Mythology is the definitive volume for anyone who wants to know the key dramas, the primary characters, the triumphs, failures, fears, and hopes first narrated thousands of years ago-and still spellbinding to this day.
Introduction to classical mythology -- Gods, the creation, and the earliest heroes -- Stories of love and adventure -- Great heroes before the Trojan War -- Heroes of the Trojan War -- Great families of mythology -- Less important myths -- Mythology of the Norsemen -- Genealogical tables.
Originally published: Boston : Little, Brown, c1942.
Includes index.
Keywords: Mythology; Mythology, Greek; Mythology, Roman; Mythology, Norse